PENGELOLAAN TAMAN NASIONAL GUNUNG LEUSER BAGIAN BUKIT LAWANG BERBASIS EKOWISATA - Robert Siburian (Jurnal Masyarakat dan Budaya, 2006)
Local people who live around National Park do not have access to participate in forest management. This condition seriously force people to pratice forest squatting and illegal logging. Illegal logging activities, for instance, having its close link with the negliance of local people to involve in National Park Management. To settle down the difference, Management of Gunung Leuser National Park at Bukit Lawang invited people who reside close to the conservation site; to take part in a program named â€œEcotourism Programâ€. Participation of people in Ecotourism Program has two purposes namely: to avoid deforestation and to generate peopleâ€™s awareness on sustainable forest management. This paper analyses two major aspecst abovementioned, that rooted closely with data collected during my fieldwork in August 2004. Keywords: Pengelolaan, Taman Nasional, Konservasi, Ekosistem dan Ekowisata,